2015
DOI: 10.1002/ccr3.195
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jiroveci prophylaxis in patients undergoing Bendamustine treatment: the need for a standardized protocol

Abstract: Key Clinical MessageThe decision for PJP prophylaxis depends on a physician's evaluation of multiple variables. The high rate of PJP infection described in this article combined with the known impaired T-cell function post Bendamustine treatment justifies considering all patients for PJP prophylaxis when they receive Bendamustine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…No treatment-related deaths were reported; however, major grade 3/4 toxicities included lymphopenia (97%), CD4 lymphopenia (91%), neutropenia (86%), and leukopenia (83%). Of note, bendamustine is associated with a reduction in CD4 lymphocyte counts and an increased risk of opportunistic infections [52].…”
Section: Advanced Stage Diseasementioning
confidence: 99%
“…No treatment-related deaths were reported; however, major grade 3/4 toxicities included lymphopenia (97%), CD4 lymphopenia (91%), neutropenia (86%), and leukopenia (83%). Of note, bendamustine is associated with a reduction in CD4 lymphocyte counts and an increased risk of opportunistic infections [52].…”
Section: Advanced Stage Diseasementioning
confidence: 99%
“…The risk of infection associated with bendamustine has yet to be fully characterized. Small series and case reports have reported the occurrence of Pneumocystis jirovecii pneumonia (PCP) and cytomegalovirus (CMV) after bendamustine exposure [19][20][21][22]. Some clinical trials suggested that bendamustine plus rituximab (BR) was associated with fewer infections than cyclophosphamide, doxorubicin, vincristine, and prednisone plus rituximab (R-CHOP) [12,13], but the same risk of infection as fludarabine and rituximab [14].…”
mentioning
confidence: 99%
“…Four cases of PJP were described in one Irish institution in patients following R‐bendamustine treatment in patients who were elderly, heavily pretreated or who received doses of bendamustine in excess of the standard 90 mg/m 2 typically used . A multicenter retrospective analysis of a cohort of patients in Israel treated with any bendamustine containing regimen over 5 years found that viral infections occurred in 11.3% of patients, of which 2.1% experienced HSV and 3.0% VZV infections . In addition, fluconazole can be prescribed in the small subset of patients, generally only older patients administered steroid containing regimens, who develop clinical thrush.…”
Section: Best Practice Guidance For Managing Patients Receiving Obinumentioning
confidence: 99%